2006
DOI: 10.1007/s10453-006-9028-9
|View full text |Cite
|
Sign up to set email alerts
|

Airborne ragweed (Ambrosia artemisiifolia L.) pollen concentrations in Croatia, 2002–2004

Abstract: The aim of this study was to determine the onset, length and end of the ragweed pollen season, taking into account diurnal, day-to-day, monthly and annual pollen variations, the effect of some meteorological parameters on atmospheric pollen concentrations and possible differences in the airborne pollen season and concentration due to sampling site. Airborne pollen was collected at three sites in central Croatia (Zagreb, Samobor and Ivanić Grad) during three pollen seasons (2002)(2003)(2004). Seven-day Hirst-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 17 publications
6
85
0
Order By: Relevance
“…Furthermore, strong associations of Ambrosia, Poaceae and Populus pollen counts with temperature and rainfall have been determined by several authors. Pollen counts were found to increase with temperature and decrease with rainfall for Ambrosia (Bartková-Ščevková, 2003;Makra et al, 2004;Peternel et al, 2006a;Piotrowska & WeryszkoChmielewska, 2006;Kasprzyk, 2008;Ščevková et al, 2010) and for Poaceae (Bartková-Ščevková, 2003;Peternel et al, 2006b;Ščevková et al, 2010). In a more detailed study, Makra et al (2011) found that an association measure is negative between the annual cycles of the daily slopes of Ambrosia and Poaceae pollen concentration trends on the one hand and the annual cycles of the daily slopes of mean temperature trends on the other hand.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, strong associations of Ambrosia, Poaceae and Populus pollen counts with temperature and rainfall have been determined by several authors. Pollen counts were found to increase with temperature and decrease with rainfall for Ambrosia (Bartková-Ščevková, 2003;Makra et al, 2004;Peternel et al, 2006a;Piotrowska & WeryszkoChmielewska, 2006;Kasprzyk, 2008;Ščevková et al, 2010) and for Poaceae (Bartková-Ščevková, 2003;Peternel et al, 2006b;Ščevková et al, 2010). In a more detailed study, Makra et al (2011) found that an association measure is negative between the annual cycles of the daily slopes of Ambrosia and Poaceae pollen concentration trends on the one hand and the annual cycles of the daily slopes of mean temperature trends on the other hand.…”
Section: Discussionmentioning
confidence: 96%
“…Counting was done using a standard sampling procedure. Pollen concentrations were expressed as number of pollen grains/m 3 of air (Käpylä & Penttinen, 1981;Peternel et al, 2006a).…”
Section: Pollen Samplingmentioning
confidence: 99%
“…Counting was performed using a standard sampling procedure. Pollen concentrations were expressed as number of pollen grains · m −3 of air (Käpylä and Penttinen, 1981;Peternel et al, 2006). Note that due to the restrictions of the sampling procedure (daily pollen counts are available after a 7-day period, respectively), applicability of the statistical models for operative pollen forecast is limited in time.…”
Section: Pollen Sampling and Countingmentioning
confidence: 99%
“…Hungary is exposed to one of the most severe air pollutions in Europe (5); in addition, airborne pollen levels here are also high. The Carpathian basin, which includes Hungary (Figure 1), is considered the most polluted region with airborne ragweed (Ambrosia artemisiifolia) pollen in Europe (6)(7)(8)(9)(10). Ragweed in Hungary discharges the most pollen of all taxa (11,12).…”
mentioning
confidence: 99%
“…Applying simple statistical analysis, several studies have detected signifi cant positive correlations of daily ragweed pollen counts with daily maximum temperature (20), daily mean temperature (6,7,(21)(22)(23), daily mean wind speed (23), and daily maximum wind speed (22) and signifi cant negative correlations with relative humidity (21)(22)(23) and rainfall (7,23,24). Furthermore, Ziska et al (25) established that the association between higher temperatures and higher ragweed pollen counts was stronger in urban than in rural locations.…”
mentioning
confidence: 99%